Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\frac{x}{17}=\frac{60}{204}=\frac{5}{17}\Rightarrow x=5\)
b)\(\frac{6+x}{33}=\frac{7}{11}\Rightarrow11\left(6+x\right)=7.33\Rightarrow11.6+11x=231\Rightarrow66+11x=231\)
\(\Rightarrow11x=231-66\Rightarrow11x=165\Rightarrow x=\frac{165}{11}=15\)
c)\(\frac{12+x}{43-x}=\frac{2}{3}\Rightarrow2\left(43-x\right)=3\left(12+x\right)\Rightarrow2.43-2x=3.12+3x\)
\(86-2x=36+3x\Rightarrow86-36=3x+2x\Rightarrow50=5x\Rightarrow x=\frac{50}{5}=10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 2x.4=128
2x =32
=> x = 5
b. 2x+1=125
2x = 125-1
2x = 124
x = 62
c. x15=x
=> x \(\in\left\{0;\pm1\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 652 + 327 + 148 + 73 = ( 652 + 148) +( 327+73) = 800+400 =1200
b) 19 x 16 x 4 + 76 x 34 = ( 19 x 4 ) x 16 + 76 x 34 = 76 x 16 + 76 x 34 = 76 x( 16+34 ) = 76 x 50= 3800
c) 136 x 68 + 16 x 2 x 136 = 136 x ( 68 + 32 ) = 136 x 100 = 13600
d) 45 x 125 - 45 x 25 + 55 x 31 + 55 x 69 = 46 x ( 125-25) + 55 x ( 31+69) = 46 x100 + 55x 100 = 4600 + 5500 = 10100
e) 125 x 25 + 125 x 74 + 125 = 125 x( 25+74 +1 ) = 125 x 100 =12500
f) 43,5 x 2015 x ( 630 - 315 x 2 ) = 43,5 x 2015 x 0 = 0
g) 0,2 x 41 x 36 + 0,8 x 9 x 58 + 1,2 x 6
= 0,2 x4 x41x 9 + 0,8 x 9 x 58 +7,2
= (0,8 x9)x 41 + ( 0,8 x 9) x 58 + 7,2 x 1
= 7,2 x 41 + 7,2 x 58 + 7,2 x 1
= 7,2 x( 41+58+1)
= 7,2 x 100 = 720.
a) 652 + 327 + 148 + 73
=(73+327)+(652+148)
=400+800
=1200
b) 19 x 16 x 4 + 76 x 34
=76*16+76*34
=76*(16+34)
=76*50
=3800
c)136*68+16*2*136
=136*68+32*136
=136*(68+32)
=136*100
=13600
d)45*125-45*25+55*31+55*69
=45*(125-25)+55*(31+69)
=45*100+55*100
=100*(45+55)
=100*100
=10 000
e)125*25+125*74+125
=125*(25+75+1)
=125*100
=12 500
còn lại bạn tự làm đi mk mỏi tay lắm rồi
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(38,7\times\left(38,7-x\right)=38,7\)
\(38,7-x=38,7:38,7\)
\(38,7-x=1\)
\(x=38,7-1\)
\(x=37,7\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : \(\frac{1}{4}+\frac{1}{3}:\frac{1}{x}=\frac{11}{12}\)
\(\Rightarrow\frac{1}{3}:\frac{1}{x}=\frac{11}{12}-\frac{1}{4}\)
\(\frac{1}{3}:\frac{1}{x}=\frac{2}{3}\)
\(\frac{1}{x}=\frac{1}{3}:\frac{2}{3}\)
\(\frac{1}{x}=\frac{1}{3}\times\frac{3}{2}\)
\(\frac{1}{x}=\frac{1}{2}\)
=> x = 2
a) \(\frac{x\div3-16}{2}+21=38\)
\(\frac{x\div3-16}{2}=38+21\)
\(\frac{x\div3-16}{2}=59\)
\(x\div3-16=59.2\)
\(x\div3-16=118\)
\(x\div3=118+16\)
\(x\div3=134\)
\(x=134.3\)
\(x=402\)
b) \(\frac{1}{4}+\frac{1}{3}\div\frac{1}{x}=\frac{11}{12}\)
\(\frac{1}{3}\div\frac{1}{x}=\frac{11}{12}-\frac{1}{4}\)
\(\frac{1}{3}\div\frac{1}{x}=\frac{2}{3}\)
\(\frac{1}{x}=\frac{1}{3}\div\frac{2}{3}\)
\(\frac{1}{x}=\frac{1}{2}\)
Vậy x = ....
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{x}{y}.\frac{3}{7}=\frac{4}{9}\)
\(\frac{x}{y}=\frac{4}{9}:\frac{3}{7}\)
\(\frac{x}{y}=\frac{4}{9}.\frac{7}{3}\)
\(\frac{x}{y}=\frac{28}{27}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)
\(x\cdot4+\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)
\(x\cdot4+\left(\frac{8}{16}+\frac{4}{16}+\frac{2}{16}+\frac{1}{16}\right)=1\)
\(x\cdot4+\frac{13}{16}=1\)
\(x\cdot4=1-\frac{13}{16}\)
\(x\cdot4=\frac{3}{16}\)
\(x=\frac{3}{16}:4\)
\(x=\frac{3}{64}\)
\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)
\(=\left(x+x+x+x\right)+\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)
\(=4x+\frac{15}{16}=1\)
\(\Rightarrow4x=1-\frac{15}{16}=\frac{1}{16}\)
\(\Rightarrow x=\frac{1}{16}:4=\frac{1}{64}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) ( x + 74 ) - 318 = 200
x + 74 = 200 + 318
x + 74 = 518
x = 518 - 74
x = 444
b ) 3636 : ( 12 . x - 91 ) = 36
12 . x - 91 = 3636 : 36
12 . x - 91 = 101
12 . x = 101 + 91
12 . x = 192
x = 192 : 12
x = 16
c ) ( x : 23 + 45 ) . 67 = 8911
x : 23 + 45 = 8911 : 67
x : 23 + 45 = 133
x : 23 = 133 - 45
x : 23 = 88
x = 88 . 23
x = 2024
d ) ( 3 . x - 6 ) + 57 = 60
3 . x - 6 = 60 - 57
3 . x - 6 = 3
3 . x = 3 + 6
3 . x = 9
x = 9 : 3
x = 3
\(a)\) \(\left(x+74\right)-318=200\)
\(x+74=518\)
\(x=444\)
Vậy x = 444
\(b)\) \(3636:\left(12x-91\right)=36\)
\(12x-91=101\)
\(12x=192\)
\(x=16\)
Vậy x = 16
\(c)\) \(\left(x:23+45\right)67=8911\)
\(x:23+45=133\)
\(x:23=88\)
\(x=2024\)
Vậy x = 2024
\(d)\left(3x-6\right)+57=60\)
\(3x-6=3\)
\(3x=9\)
\(x=3\)
Vậy x = 3
Ta có:
x − 16 = 17 , 98 + 145 , 2 x − 16 = 163 , 18 x = 163 , 18 + 16 x = 179 , 18
Vậy x = 179,18.
Đáp án D